2020
DOI: 10.18331/brj2020.7.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Selective evaporation of a butanol/water droplet by microwave irradiation, a step toward economizing biobutanol production

Abstract: Selective evaporation of a butanol/water droplet by microwave irradiation, a strategy to economize biobutanol production.Journal homepage: www.biofueljournal.com HIGHLIGHTS ➢Surface and evaporation of alcohol/water was studied in-situ in response to microwave irradiation. ➢Butanol content in liquid phase was reduced by approx. 90%. ➢Similar trend was observed with pentanol/water droplet. ➢The method could be applied to improve efficiency of fermentative butanol separation. GRAPHICAL ABSTRACT ARTICLE INFO ABSTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…12 The enhancement of alcohol at the water surface 13 also increased the formation of voids and nano-bubbles during MW. 14 Glucose solution. Figure 3 shows pro les of refractive index during the irradiation of different power.…”
Section: Resultsmentioning
confidence: 99%
“…12 The enhancement of alcohol at the water surface 13 also increased the formation of voids and nano-bubbles during MW. 14 Glucose solution. Figure 3 shows pro les of refractive index during the irradiation of different power.…”
Section: Resultsmentioning
confidence: 99%
“…With high MW power, some of the decane droplets were visible at the top of the pendant drop. In previous studies, [ 33,34 ] it has been shown that the surface tension was quickly reduced with MW irradiation. The impact of de‐emulsification that is, bubble bursting at the surface, is expectedly weak during MW irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…The droplet shape was extracted and analyzed to produce surface tension. [ 33 ] The analysis was applied during and after the irradiation. Moreover, the surface tensions at different decane concentrations (5, 10, and 15 vol.…”
Section: Methodsmentioning
confidence: 99%
“…37 Predicting the interfacial composition at elevated temperatures is essential to calculate the evaporation rate of the binary droplet. 41,42 3.2. Nonaqueous Solvents.…”
Section: Influence Of Temperaturementioning
confidence: 99%